PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL PADA EMPLOYEE ENGAGEMENT Studi di Pemerintah Provinsi DKI Jakarta - , RINDI ANTIKA; , Tarsisius Hani Handoko, Dr. MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of the research is to examine and analyze how significant transactional and transformational leadership affect the employee management in DKI Jakarta government. The method used in this research is hypothesis testing. This research use two independent variables, transactional leadership (X1) and transactional leadership (X2), whereas employee engagement (Y) as dependent variable. The population of the research is all employees in DKI Jakarta government with employee working in City Hall after the governor of DKI Jakarta 2012-2017 inaugurated as the sample. Data collection is carried out by giving out questionnaire to 129 respondents. The sampling of the research is purposive sampling, whereas the method of data analysis is multiple regression analysis. Based on the result of the research, it is found that (1) Transactional leadership positively and significantly affects employee engagement of the employee in DKI Jakarta government. (2) Transformational leadership positively and significantly affects the employee engagement of DKI Jakarta government.